Effects of γ Irradiation on Leaf Blight Disease of Some Taro (Colocasia esculenta L. Schott) Genotypes - Sahoo, B. B.; Kole, P. C.; Sahoo, M. R. (International Journal of Bio-resource and Stress Management, 2023)
The healthy mature seed cormels of 10 diverse genotypes of taro were subjected to 10Gy γ- irradiation. The mutant populations were evaluated for Phytophthora leaf blight disease under in vitro and in vivo disease conditions along with their non-irradiated mother genotypes. The results revealed that variability (range and standard deviation) in mutant populations were more than their mother populations. Under in vitro Phytophthora leaf blight conditions, the blight incidence such as spot diameter and number of sporangia produced was minimized with γ-irradiation as compared to the non-irradiated leaf samples. It indicated that γ-rays suppressed the growth of Phytophthora spores in the leaf tissues of taro. The genotypes TSL and Duradim showed resistance consistently against leaf blight both under irradiated and non-irradiated conditions. The disease incidence was also minimized in the tested susceptible lines under γ-irradiation under artificial epiphytotic conditions. The yield reduction due to blight infestation in irradiated plants was lower, compared with the non-irradiated plants. Association of desirable mutations with undesirable mutations led to the problem of linkage drag as these cannot be separated because of vegetative propagation. γ-irradiation in high yielding susceptible lines such as Telia and Satasankha Local may help in inducing resistance against leaf blight with no/low yield loss due to infestation of Phytopthora colocasiae.